Resiliensi Anggota Majelis Bahasa (MASA) dalam Menghadapi Tekanan Akademik dan Tuntutan Organisasi Secara Bersamaan - Triana Auliaunissa; Syafina El Qolbina; Aulia Sabila Rahmadani; Fajar Indah Nuryanti; Siti Hikmah (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study explores the resilience of members of Majelis Bahasa (MASA) in balancing academic pressure and organizational responsibilities simultaneously, emphasizing how their adaptive strategies support sustained performance. Using a qualitative approach, the research captures members’ experiences in managing overlapping demands, emotional tension, and fluctuating workloads through reflective coping, flexible scheduling, and collaborative support. The findings reveal that resilience among MASA members emerges as a dynamic developmental process rather than a static trait, shaped by continuous negotiation between personal capacity and contextual challenges. Participants consistently reported that peer guidance, shared responsibility, and structured communication played crucial roles in strengthening their endurance during high-pressure periods. Academic obligations often intersected with organizational duties, yet members demonstrated an ability to recalibrate priorities, reinterpret difficulties, and derive motivation from collective identity. These dynamics highlight that resilience in student organizations is built through accumulated experience, supportive networks, and meaningful engagement in literacy-driven initiatives. The study contributes to a deeper understanding of how student-led environments cultivate sustainable resilience in complex academic ecosystems.